Chelation‐driven Regioselective 1, 2‐Dearomatizations of N‐Aromatic Zwitterions. (10th February 2021) - Ko, Donguk; Kim, Jiyoung; Lee, Jiyoun; Yoo, Eun Jeong
Abstract : In this study, several dearomative reactions of N‐aromatic zwitterions were carried out to determine the factors controlling site selectivity. A series of organometallic species were applied as nucleophiles for dearomative additions, which revealed that chelation between metal and nitrogen anion dominantly affected the site selectivity of the dearomative reaction in N‐aromatic zwitterions. A cascade process, involving dearomative addition followed by intermolecular cyclization, to synthesize fused cyclic molecules was also demonstrated using ylides, which were selected as capable chelation substrates. Abstract : Regioselective 1, 2‐dearomatizations of N‐aromatic zwitterions and organometallic nucleophiles have been achieved by the chelation strategy leading to the proximity of substrates. It has also been observed that sulfonium ylide, which could strongly coordinate with nitrogen anions, was applicable as a nucleophile, leading to [5 + 1] cycloadditions.